ANALYSIS OF INVESTMENTS ROLE IN THE ECONOMIC DEVELOPMENT - Ruzieva Elvira Abdulmitovna; Nurgaliyeva Aliya Miyazhdenovna; Duisenbayeva Botagoz Baimukhanbetova; Assanova Altynay Bolysovna; Shtiller Marina Vladimirovna (Scientific Journal of Pedagogy and Economics, 2019)
The impact of investment on a country's economic growth is obvious. For example, the net investment indicator is one of the indicators of the state’s economic development. A decrease or increase in investment leads to changes in the level of production and incomes in the country, which, in turn, stimulate or contribute to a decline in economic growth. On this basis, attracting foreign investment is of interest to all countries, and along with the use of domestic investment contributes to the economic development of the state. In the economic literature presents a lot of studies on the impact of investment on the economic growth of the country. However, mainly in the works the analysis is presented directly on the author’s country and the influence of mostly only direct foreign investments on the state’s GDP is considered. However, the authors did not pay attention to the impact of portfolio investment, as well as the primary investment income on the economic growth of the countries of the world in a comparative aspect. In this article, the authors attempted to conduct a comparative analysis of the effects of direct and portfolio investments, as well as of the initial income from investments and net errors on the GDP of some countries of the world, both in the far and near abroad.